Shuangxinfang Prevents S100A9-Induced Macrophage/Microglial Inflammation to Improve Cardiac Function and Depression-Like Behavior in Rats After Acute Myocardial Infarction - Sun, Yize; Wang, Zheyi; Hou, Jiqiu; Shi, Jinyu; Tang, Zhuoran; Wang, Chao; Zhao, Haibin (Frontiers in Pharmacology, 2022)
Background: Shuangxinfang (Psycho-cardiology Formula, PCF) was reported to alleviate myocardial ischemia injury and improve depression-like behavior. Interestingly, our previous proteomics study predicted that the protein S100A9 appeared as an important target, and macrophage/microglial inflammation might be involved in the process of PCF improving depression induced by AMI. The aim of this study is to validate the proteomics results. Methods: AMI rat models were established, followed by the administration of PCF or ABR-215757. FST and OFT were applied to record depression-like behavior, and echocardiography was employed to evaluate cardiac function. Morphological changes of cardiomyocytes were assessed by HE staining and TUNEL staining, as well as masson trichrome staining. Hippocampal neurogenesis was determined by Nissl staining, while 5-HT and BDNF were analyzed as biochemical indicators of depression. We employed RT-qPCR, western blotting and immunofluorescence to detect the expression of pathway-related gene and protein. Expression of inflammatory factors were performed by ELISA. The activation of macrophage and microglia was assessed via immunoreaction respectively using CD68 and Iba1. BV2 cells were primed with recombinant protein S100A9, then treated with PCF serum or ferulic acid, to determine microglial inflammation. Results: Rats in the AMI group showed heart function deterioration, as well as depression-like behavior. Coronary ligation not only brought about myocardial inflammation, cell apoptosis and fibrosis, but also reduced the neurogenesis, and decreased the content of 5-HT. PCF could ameliorate the pathological and phenotypic changes of the heart and brain, and inhibit the expression of S100A9 protein, the activation of microglial cell and the secretion of IL-1β and TNF-α raised by AMI. ABR-215757 showed therapeutic effect and molecular biological mechanisms similar to PCF. Pretreatment with PCF serum or ferulic acid in vitro was proved to efficiently block the hyperactivation of BV2 cells and increasement of cytokine contents induced by recombinant protein S100A9. Conclusion: We identify S100A9 as a novel and potent regulator of inflammation in both heart and brain. Macrophage/microglia inflammation mediated by S100A9 is considered as a pivotal pathogenic in depression post-AMI, as well as a major pathway for the treatment of PCF, suggesting that PCF is a promising therapeutic candidate for psycho-cardiology disease.